2017
DOI: 10.1002/ejic.201700833
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Four Indium‐Based Heterometallic Metal–Organic Frameworks Containing Intersecting Indium–Organic Helical Chains and Different Divalent‐Metal‐Ion Linkers

Abstract: Four indium‐based heterometallic metal–organic frameworks In3M(IMDC)3(NO3)2(H2O)6·solvent (2‐M, M = Mn, Co, Zn, Mg, H3IMDC = imidazole‐4,5‐dicarboxylic acid) have been made under solvothermal conditions, and are characterized by single‐crystal X‐ray diffraction studies, energy‐dispersive X‐ray spectroscopy, infrared spectroscopy, thermogravimetric analysis, and powder X‐ray diffraction analysis. Structural analysis indicates that 2‐M exhibit 3D porous frameworks generated by linking three intersecting 1D In–IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In the absence of acetic acid, compound 1 could not be obtained under similar conditions. It can also be seen that the N atom disconnects from the In 3+ center, which may be a potential coordination site for further enhancing the stability of the MOFs by the formation of In–N bonds. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of acetic acid, compound 1 could not be obtained under similar conditions. It can also be seen that the N atom disconnects from the In 3+ center, which may be a potential coordination site for further enhancing the stability of the MOFs by the formation of In–N bonds. , …”
Section: Resultsmentioning
confidence: 99%
“…In this process, TM 2+ -N MOFs are usually more stable than TM 2+ -carboxylate MOFs. Tetravalent and trivalent TM cations, such as Zr 4+ and In 3+ , usually tend to form MOFs with TM-O coordination modes by forming six- to eight-coordinate environments. However, in comparison to the number of TM 2+ - and Zr 4+ -based MOFs, In 3+ -based MOFs are comparatively fewer in number in literature reports. In this field, the In 3+ ions were used to react with organic di-, tri-, and tetracarboxylic ligands, resulting in several In-based 2D and 3D frameworks, which have been widely used for gas separation, pollutant removal, and catalytic reactions. , Among these structures, it could be found that most of the In 3+ centers tend to coordinate with carboxylate oxygen atoms, although several ligands contain N and S heteroatoms. ,,, To date, the design and synthesis of In-based framework materials are still in their infancy and represent a promising way to construct stable MOFs for various applications, especially for introducing polydentate ligands with both carboxylate and N-heterocyclic rings into the In-MOFs to promote the formation of In–N bonds …”
Section: Introductionmentioning
confidence: 99%
“…Recently, two types of isomorphic indium-based heterometallic organic frameworks built by 1,3,5-benzenetricarboxylic acid and imidazole-4,5dicarboxylic acid have been synthesized in our gourp. 14,15 Herein, we designed and synthesized two novel heterometallic cluster-based organic frameworks built from trinuclear indium a n d c u p r o u s h a l i d e c l u s t e r s , i . e .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the heterometallic MOFs constructed from indium and copper iodide clusters remain at the beginning. Recently, two types of isomorphic indium-based heterometallic organic frameworks built by 1,3,5-benzenetricarboxylic acid and imidazole-4,5-dicarboxylic acid have been synthesized in our gourp. , Herein, we designed and synthesized two novel heterometallic cluster-based organic frameworks built from trinuclear indium and cuprous halide clusters, i.e., [(In 3 O) 2 (Cu 2 I 2 ) 3 (ina) 12 (H 2 O) 6 ]­(NO 3 ) 2 ·7DMA·10H 2 O ( 1 ) and [NH 2 (CH 3 ) 2 ]­[In 3 (OH) 2 (H 2 O) 2 (ina) 8 (Cu 4 I 4 ) 2 ]·5DMA·8H 2 O ( 2 ). Interestingly, 1 displays a 3D cationic skeleton, which is built from a planar [In 3 O­(CO 2 ) 6 ] trimer and a rhombohedral Cu 2 I 2 cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), which are built by rationally connecting the functional organic linkers with inorganic metal nodes, have shown promising applications and potentials in many fields, such as fluorescence sensing, gas adsorption separation, catalytic, and so on . MOFs have demonstrated several advantages including rational preparation, good chemical stability, high surface area, and highly selective pores with specific size and shape ,. The rational designed linkers and crystal engineering theory make MOFs excellent candidates for the construction of multi‐responsive luminescent materials with remarkable sensing abilities…”
Section: Introductionmentioning
confidence: 99%